2008
DOI: 10.1176/appi.ajp.2007.05081484
|View full text |Cite
|
Sign up to set email alerts
|

The Prospective Course of Rapid-Cycling Bipolar Disorder: Findings From the STEP-BD

Abstract: While DSM-IV rapid cycling was prospectively observed in only a small percentage of patients, the majority of these patients had continued recurrences at lower but clinically significant rates. This suggests that cycling is on a continuum and that prevention of recurrences may require early intervention and restricted use of antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
115
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 19 publications
7
115
0
8
Order By: Relevance
“…6 However, controversy still exists, with one study having reported later age at onset for RC 28 and other studies reporting no difference in age at onset between RC and NRC. 7,29,30 Another finding of the present study that is consistent with the literature is the higher number of suicide attempts and the higher proportion of suicide attempters in the RC group. 4,6,13,14 This might be explained by the usually longer duration of disease associated with RC, which would be related to the earlier age at onset discussed above.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…6 However, controversy still exists, with one study having reported later age at onset for RC 28 and other studies reporting no difference in age at onset between RC and NRC. 7,29,30 Another finding of the present study that is consistent with the literature is the higher number of suicide attempts and the higher proportion of suicide attempters in the RC group. 4,6,13,14 This might be explained by the usually longer duration of disease associated with RC, which would be related to the earlier age at onset discussed above.…”
Section: Discussionsupporting
confidence: 91%
“…[37][38][39] Our study corroborates the notion that hypothyroidism and hyperthyroidism are not associated with RC. Confirming the findings of numerous previous studies, 6,7,13,17,20,38 we observed a higher rate of antidepressant use in the RC group. Some authors have found that the likelihood of cycling increases linearly with antidepressant use, with patients taking antidepressants being over three times more likely to have RC than patients who do not use antidepressants.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…23 Another vital clinical observation examines the prospective course of rapid-cycling in BD. 24 Using a convenience sample of enrollees (n = 1742), mood episodes were prospectively observed. Among the 1742, 32% had experienced rapid cycling in the year preceding the STEP-BD study, and 32% dropped out before 1 year of treatment was completed.…”
Section: Observations On Bipolar Depression From the Standard Care Pamentioning
confidence: 99%